EVALUASI IMPLEMENTASI KURIKULUM MERDEKA DENGAN MODEL CIPP (CONTEXT, INPUT, PROCESS, PRODUCT) : Studi Di Madrasah Aliyah Negeri Se Kabupaten Pandeglang - Setiawan, Iwan; Anis Zohriah; Anis Fauzi (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2024)
The State Islamic Senior High Schools in Pandeglang District serve as a pilot project for the implementation of the Free Curriculum in the academic years 2022/2023 and 2023/2024. Therefore, it is necessary to evaluate the extent of the Free Curriculum implementation in these schools using the CIPP model to assess its effectiveness.This evaluative study adopts a qualitative descriptive approach involving school principals, vice principals, teachers, and students as informants. Data collection methods include interviews, documentation, and observation. Data validity is ensured through meticulous observation and triangulation from various sources, methods, and theories. Data analysis is conducted using qualitative analysis techniques. The objective of this research is to assess the implementation of the Free Curriculum program using the CIPP model in State Islamic Senior High Schools in Pandeglang District, determining whether the program should continue or be discontinued based on certain considerations.The findings of the evaluation using the CIPP model reveal several key points. The Context evaluation indicates strong environmental support, but teacher understanding remains heterogeneous. Input evaluation highlights the quality of curriculum documents and the need for human resource improvement. The teaching process is still suboptimal, particularly in differentiated learning approaches. The outcomes include student learning achievements and P5 and P2RA, which exceed the Minimum Completion Criteria for Learning Objectives (KKTP). However, the program can be continued with recommendations for improvement. By considering these recommendations, the implementation of the Free Curriculum program in State Islamic Senior High Schools in Pandeglang District can be enhanced to achieve better educational outcomes for students.